Evaluation of polycyclic aromatic hydrocarbons (PAHs) in moringa oleifera leaves and infusion - Azrina Aziz; Khairiah Abd Karim; Mohd Azmier Ahmad; Mohamad Jemain Mohamad Ridhwan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Moringa oleifera infusion is a popular drink among herbal infusion consumers. Although M. oleifera is claimed to have medicinal value and promoted health benefits, it does not be simply considered safe if no specific study is conducted to determine Polycyclic aromatic hydrocarbons (PAHs) content in commercial M. oleifera herbal drink. Therefore, this study was conducted to investigate 10 PAHs content in M. oleifera dried leaves and in its infusion. The second objective was to assess the effect of mass-volume ratio on PAHs content in M. oleifera infusion. PAHs extraction procedure was performed using QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) method. PAHs determination and quantification were performed using Gas Chromatography and Flame Ionization Detector (GC-FID). The mean of total 10 PAHs (∑10PAH) in M. oleifera dried leaves and infusion ranged from 1.06 µg/kg to 5.51 µg/kg and 0.62 µg/kg to 4.80 µg/kg, respectively. Four different mass-volume ratios were used in this study to determine PAHs content that could be extracted from M. oleifera dried leaves into an infusion; 2:250, 20:250, 10:100, and 10:50. The ratio of 2:250 showed the lowest PAHs content in comparison with other ratios. The PAHs content in M. oleifera dried leaves and infusion have statistically significantly different (p > 0.01) from each other. The toxic equivalency quotient (TEQ) value of M. oleifera dried leaves and infusion ranged from 0.01 to 0.09 and 0.00 to 0.07, respectively. PAHs content in M. oleifera dried leaves and infusions complied with the maximum limit set by Commission Regulation (EU) No. 2015/1933.